Oswald Mathias Ungers: dialectical principles of design. Issue 7 (17th November 2018) - Jacoby, Sam
Abstract : An important contributor to the post-war debate on architecture's relationship to the city was the German architect Oswald Mathias Ungers (1926–2007). Starting in the early 1960s, he became increasingly interested in questions of typological organisation and morphological transformation, positing their relationship in dialectical principles. This article traces some of the shifts in Ungers's understanding of architecture through a utilisation of typology as a design theme, the morphological transformation of architectural form and the coincidence of opposites in urban building complexes. It does this by reviewing a selection of closely linked pieces of design research (lectures, writings and large-scale housing projects) from the 1960s to 1980s. The paper also examines how Ungers's interest in rational design as a problem of serial formal and social transformations led him to new understandings of architectural and urban design. The concepts of typology and morphology hereby played a central role in reclaiming architecture as a formal and intellectual, but also a social and imaginative project, through which the city could be reasoned, always, however, through the problems arising from architectural form itself.